Internationalisation of the Malaysian Wooden Furniture Industry - Zhao, LiXu (2016)
Malaysia has a strong market share in wooden furniture and the witnessed fast growth made it a leading furniture exporter. Currently, Malaysia is the 8th largest furniture export country. As an export dominated industry, the wooden furniture industry occupies a significant position in the Malaysian economic development. Since the industry is a challenged and deteriorating in global competition, the research objective is to evaluate the present situation and find out strategies on how to improve the Malaysian wooden industry's competitiveness. Accordingly, the research question aim to explore internationalism motivations, advantages, issues, actions in Malaysian wooden furniture industry. Dunning's ecletic paradigm and Porter's value chain were adopted as basic theories in the current study. The main findings from this project indicates that the challenges of labour shortage, raw materials and product design issues are mostly influencing the development of the Malaysian wooden furniture industry. Meanwhile, it was observed that issues exist in any stages in the manufacturing value chain may influence the performing efficiency. Thus, the government, national institutions and wooden furniture manufacturers need to rapidly take labour, design and raw materials alternatives and innovative design approaches to promote the performance of the Malaysian wooden furniture in the global market.